2022
DOI: 10.1108/jstpm-07-2021-0095
|View full text |Cite
|
Sign up to set email alerts
|

Achieving an agile organisation in an Indonesian telecommunications company: investigation on leadership impact and mediation variables

Abstract: Purpose Agility is an important characteristic that every organisation requires in today’s competitive digital era. Telecommunications companies in Indonesia face various types of competition, both from the same industry and new models. This study aims to identify the agility level of telecommunications companies in Indonesia. It also examines the effect of leadership style directly and indirectly through the mediation of employee readiness, innovation culture, technology capability and organisational structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 76 publications
(110 reference statements)
0
7
0
Order By: Relevance
“…The study emphasizes that both organizational factors and individual factors affect the readiness for organizational change (Wanberg and Banas, 2000;Judge et al, 1999). Its findings highlight that each of the eight factors, namely experience of change, trust in management, social relationships at workplace, commitment towards organization, organizational support, participation in decision-making, leadership and communication system, independently have a significant effect on readiness for organizational change (Goksoy, 2012;Rafferty and Simons, 2006;Hanpachern et al, 1998;Madsen et al, 2005;Susanty et al, 2022). It can also be concluded that experience of change, commitment towards organization and participation in decision making are more pertinent than other factors that affect readiness for organizational change (Armenakis et al, 1993;Eby et al, 2000).…”
Section: Conclusion and Managerial Implicationsmentioning
confidence: 90%
“…The study emphasizes that both organizational factors and individual factors affect the readiness for organizational change (Wanberg and Banas, 2000;Judge et al, 1999). Its findings highlight that each of the eight factors, namely experience of change, trust in management, social relationships at workplace, commitment towards organization, organizational support, participation in decision-making, leadership and communication system, independently have a significant effect on readiness for organizational change (Goksoy, 2012;Rafferty and Simons, 2006;Hanpachern et al, 1998;Madsen et al, 2005;Susanty et al, 2022). It can also be concluded that experience of change, commitment towards organization and participation in decision making are more pertinent than other factors that affect readiness for organizational change (Armenakis et al, 1993;Eby et al, 2000).…”
Section: Conclusion and Managerial Implicationsmentioning
confidence: 90%
“…Digitalization helps companies in customizing products as per customer needs, changing business values and increasing focus to meet customer expectations for product quality and service standards (Xiu et al, 2017;Tsou and Chen, 2021). However, digitalization is also pushing people in organizations to change faster, which promotes the urgency for digital readiness (Tabrizi et al, 2019;Jun et al, 2021;Susanty et al, 2022). The help of talent development leads to the development of a lot of positive attitudes within the employee, such as an increase in motivation (Panda and Sahoo, 2015;Sheel and Nath, 2019).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…The roots of a firm's innovative capability may be derived from talent development processes. As employees' knowledge, skills and competencies are maximized and developed, they add value to the firm by possessing the capacity to yield innovative ideas, which may lead to new and improved products and services (Dibrell et al, 2014;Susanty et al, 2022). Based on these arguments, the suggested hypothesis is: H3: Talent Development has a positive and significant impact toward Innovativeness.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
See 2 more Smart Citations